1986
DOI: 10.1017/s0033291700010370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the prevalence of abnormal eating attitudes among Arab female students of both London and Cairo Universities

Abstract: SynopsisTwo matched samples of Arab female undergraduate students attending London and Cairo Universities were recruited to determine the relative prevalence of abnormal eating attitudes and the effect of exposure to Western culture upon this prevalence. A positive response was reported on the Eating Attitudes Test (EAT-40) in 22% of the students in the London group and 12% in the Cairo group, indicating that abnormal attitudes occur in this non-Western population. Six cases among the London sample fulfilled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(132 citation statements)
references
References 16 publications
7
122
2
1
Order By: Relevance
“…These findings support the idea that deep-seated acculturative processes may play an important role in the development of eating disorders amongst immigrant populations (Davis & Katzman, 1999;Nasser, 1986;T. N. Robinson et al, 1996) and those living through rapid sociocultural transition (Abou-Saleh et al, 1996;Al-Adawi et al, 2002;Al-Subaie, 2000;Gordon, 2001).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These findings support the idea that deep-seated acculturative processes may play an important role in the development of eating disorders amongst immigrant populations (Davis & Katzman, 1999;Nasser, 1986;T. N. Robinson et al, 1996) and those living through rapid sociocultural transition (Abou-Saleh et al, 1996;Al-Adawi et al, 2002;Al-Subaie, 2000;Gordon, 2001).…”
Section: Discussionsupporting
confidence: 72%
“…She further argues that, in such circumstances, some individuals "resort to the 'body' as a new medium for expressing this cultural confusion and distress" (p. 347). This idea of a relationship between eating disorders and acculturative stress is supported by higher rates of eating disorders symptoms amongst ethnic minority and immigrant populations within Western nations (Davis & Katzman, 1999;Nasser, 1986;T. N. Robinson et al, 1996).…”
Section: Implicit Out-group Preference and Eating Disorders Symptoms mentioning
confidence: 99%
“…35 To our knowledge, no epidemiological studies of eating-related attitudes, preoccupations, and psychological traits among Israeli-Arab schoolgirls have been conducted in Israel. The focus of the current study was to investigate the prevalence of disordered eating attitudes and behaviors, including weight concerns, dieting, and eating behaviors, using the EDI-2, in a group of Arab schoolgirls in Israel according to three religious subgroups (Moslems, Druze, and Christians) and three age subgroups (age ranges, 12-13, 14-15, and [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…15 Thus, it is not surprising that low rates of ED have been reported among Arab populations. 3,4,[16][17][18] A few studies examining the prevalence of eating disorders have been conducted in Arab cultures, including two studies that reported cases of BN in Pakistan. 19,20 In another study on female Arab students in London and Cairo Universities, Nasser 18 found that 12% of the participants in the London group met Russell's 21 criteria for BN, whereas none of the Cairo group reported bulimic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Potential mediators between social change and risk for disordered eating are incompletely understood. They include a new relative abundance of food, 7 greater exposure to mass media, 13 and acculturation.…”
Section: Introductionmentioning
confidence: 99%